Education teacher training. Socio-personal skills according to the gender and educational stage - L. López Hernáez; C. Sabater Fernández (Universitat Politècnica de València, 2019)
The aim of this study is to assess the level of self-realization and personal growth of teachers in training in two Spanish Universities, one located in the north -University of La Rioja- and other in the south -University Catholic Murcia-. The sample consists of 366 teachers in training, 183 future teachers in the primary stage belonging to the University of La Rioja, and 183 belonging to the pre-school stage at the Catholic University of Murcia. The "Questionnaire Self-concept and realization" -AURE- (Domínguez, 2001; Aciego, Domínguez and Hernández, 2005) is used, and the results show that future primary school teachers -which teach students between 7 and 12 years oldshow favorable levels in self-realization and personal growth. However, these measures are significantly lower compared to future teachers of pre-schools education -that teach students between 3 and 6 years old-. There are also differences by gender, significantly higher in the women future teachers of pre-school. These data indicate a more urgent need to strengthen programs based in emotional skills among men and among those who teach the older students.